Current status of radiation grafted membranes for fuel cells in Malaysia - Ahmad, Arshad (2015)
As one of the most versatile energy solutions ever invented, fuel cells are able to generate clean, efficient and reliable power for almost any device requiring electricity and because of that, it has significant roles to play in a number of energy end-use sectors from electric vehicle to power plant. In the near future, fuel cell will power our cars with hydrogen replacing the petroleum fuel that is used in most vehicles today.